Emotional Hazard and Real Effort in a Power-to-Take Game - Ronald Bosman; Matthias Sutter; Frans van Winden (Tinbergen Institute, 2000)
This paper experimentally investigates whether agents behavedifferently if their own earnings are atstake (effort experiment) or a budget that is provided to them likea sort of manna from heaven(no-effort experiment) . We use the so-called power-to-take game,employed by Bosman & VanWinden (1999) to study the impact of emotions on economic behavior.Players are randomly dividedinto pairs consisting of a take authority and responder. Both playersin each pair have an endowment. The game consists of two stages. In the first stage, the takeauthority decides how much of theendowment of the responder that is left after the second stage willbe transferred to the take authority(the so-called take rate). In the second stage, the responder canpunish the take authority by destroying (part of) his or her endowment.Our main findings are the following:responders destroy moreoften and a greater amount on aggregate in the no-effort experiment;responders more often choosean intermediate amount of destruction in the no-effort experiment;the behavior of take authorities does not depend on effort;responders expect lower take rates in the no-effort experiment;in addition to the take rate, responders' expectations of the take ratehave a significant effect on theprobability of punishment in both the effort and no-effortexperiment. We explain these results withthe help of emotion theory.
Keywords: 330; Spieltheorie; Theorie